Prognostic scoring systems and comorbidities in chronic myelomonocytic leukaemia: a nationwide population‐based study. (5th June 2020) - Moreno Berggren, Daniel; Kjellander, Matilda; Backlund, Ellen; Engvall, Marie; Garelius, Hege; Lorenz, Fryderyk; Nilsson, Lars; Rasmussen, Bengt; Lehmann, Sören; Hellström‐Lindberg, Eva; Jädersten, Martin; Ungerstedt, Johanna; et al.
Summary: Outcomes in chronic myelomonocytic leukaemia (CMML) are highly variable and may be affected by comorbidity. Therefore, prognostic models and comorbidity indices are important tools to estimate survival and to guide clinicians in individualising treatment. In this nationwide population‐based study, we assess comorbidities and for the first time validate comorbidity indices in CMML. We also compare the prognostic power of: the revised International Prognostic Scoring System (IPSS‐R), CMML‐specific prognostic scoring system (CPSS), MD Anderson Prognostic Scoring System (MDAPS) and Mayo score. In this cohort of 337 patients with CMML, diagnosed between 2009 and 2015, the median overall survival was 21·3 months. Autoimmune conditions were present in 25% of the patients, with polymyalgia rheumatica and Hashimoto's thyroiditis being most common. Of the tested comorbidity indices: the Charlson Comorbidity Index (CCI), Haematopoietic cell transplantation‐specific Comorbidity Index (HCT‐CI) and Myelodysplastic Syndrome‐Specific Comorbidity Index (MDS‐CI), CCI had the highest C‐index (0·62) and was the only comorbidity index independently associated with survival in multivariable analyses. When comparing the prognostic power of the scoring systems, the CPSS had the highest C‐index (0·69). In conclusion, using 'real‐world' data we found that the CCI and CPSS have the best prognostic power and that autoimmune conditions are overrepresented in CMML.